Voices from the Field: School Leadership in Special Education - Zaretsky, Lindy; Moreau, Louise; Faircloth, Susan (Alberta Journal of Educational Research, 2008)
This study focuses on four key issues: the perception of the role played by principals in Ontario in the administration and supervision of special education programs and services; the extent to which the construct of the principal as the instructional leader accurately depicts the role of the principal in schools with high concentrations of students with special needs; the knowledge and skills needed by principals for them to assume responsibility for the administration and supervision of special education programs and services in school contexts of diversity and difference; and the [re]structuring of leadership preparation programs to bridge the gap between current knowledge and leadership/classroom practice.